1983
DOI: 10.1002/jat.2550030209
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen and its toxicity

Abstract: Acetaminophen (APAP) is considered one of the safest of all minor analgesics, but when taken in large doses (greater than 10 g) toxicity occurs. Severely poisoned patients experience hepatic and/or renal failure. The major metabolic pathway of APAP is formation of glucuronide and sulfate conjugates. A minor pathway is formation of a reactive metabolite that conjugates with glutathione (GSH). When GSH is depleted, the reactive metabolite causes necrosis of hepatic and other tissues. Treatment of APAP toxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 88 publications
4
42
0
Order By: Relevance
“…Experiments were undertaken to investigate the role of GSH depletion in glycogenolysis and ascorbate synthesis. GSH deficiency was provoked by various agents: the thiol oxidant, diamide [14], the strong NADPH consumer compound, menadione [15], the specific inhibitor of T-glutamylcysteine synthetase, buthionine sulfoximine [16], the GSH conjugative acetaminophen [17] and dibutyryl cyclic AMP [18]. It was demonstrated that various agents which depleted GSH in hepatocytes, cause an increased ascorbate production via increased glycogenolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were undertaken to investigate the role of GSH depletion in glycogenolysis and ascorbate synthesis. GSH deficiency was provoked by various agents: the thiol oxidant, diamide [14], the strong NADPH consumer compound, menadione [15], the specific inhibitor of T-glutamylcysteine synthetase, buthionine sulfoximine [16], the GSH conjugative acetaminophen [17] and dibutyryl cyclic AMP [18]. It was demonstrated that various agents which depleted GSH in hepatocytes, cause an increased ascorbate production via increased glycogenolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Paracetamol is metabolized primarily in the liver and eliminated by conjugation with sulfate and glucuronide, and then excreted by the kidney. Moreover, paracetamol hepatotoxicity has been attributed to the formation of toxic metabolites, when a part of paracetamol is activated by hepatic cytochrome P-450 to a highly reactive metabolite Nacetyl-p-benzoquinoneimine 26 (NAPQI). Toxic metabolites (N-acetyl-p-benzoquineimine) can alkylate and oxidise intracellular GSH, which results in liver GSH depletion subsequently leads to increased lipid peroxidation by abstracting hydrogen from a polyunsaturated fatty acid and ultimately, liver damage due to higher doses of paracetamol.…”
Section: Discussionmentioning
confidence: 99%
“…51 While AP is metabolized in the liver to primarily nontoxic glucuronide and sulfate conjugates, a minor metabolic pathway involves oxidation by CYP2E1 to form a reactive metabolite, N-acetyl-p-benzoquinoneimine, which is either detoxified by conjugating with reduced GSH or binds to hepatic macromolecules covalently. 18 With overdoses, the conjugation pathways become saturated and the GSH level decreases, leaving the reactive metabolite free to bind with hepatic macromolecules, resulting in hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…AP, which is widely used as an analgesic and antipyretic agent, is also hepatotoxic in very high doses. 15 The hepatotoxicity of CCl 4 16-17 and AP 18 is caused by reactive intermediates (trichloromethyl radical for CCl 4 ; N-acetyl-pbenzoquinoneimine for AP) produced during their metabolism chiefly by CYP2E1 in the liver.…”
mentioning
confidence: 99%